TATA KELOLA MANAJEMEN PENDIDIKAN BERBASIS TOTAL QUALITY MANAGEMENT (TQM) - Rita Hastuti; Cecep Hilman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low quality of education in several educational institutions indicates the need for well-directed, systematic, and continuously improvement-oriented management governance. This study aims to analyze the concepts, principles, and implementation of Total Quality Management (TQM) in educational management governance to enhance educational quality. The research method employed is a literature study, with data collected through a review of books, national and international journal articles, and relevant educational policy documents, which were analyzed using descriptive qualitative content analysis techniques. The findings indicate that the TQM concept positions quality as the primary orientation through stakeholder satisfaction and continuous improvement. The implementation of TQM principles contributes to strengthening planning, organizing, implementation, and evaluation processes in educational quality management in a systematic manner. This study concludes that TQM-based educational management governance is a relevant and strategic approach for promoting sustainable improvement in educational quality.